Application of Polyethylene/Polypropylene Glycol Ethers of Fatty Alcohols for Micelle‐Mediated Extraction of Calendula anthodium. Issue 3 (26th December 2018) - Śliwa, Karolina; Śliwa, Paweł; Sikora, Elżbieta; Ogonowski, Jan; Oszmiański, Jan; Nowicka, Paulina
Abstract: Classical extraction methods used for the isolation of active substances from the plant materials are expensive, complicated, and often environmentally unfriendly. The ultrasonic assisted micelle‐mediated extraction (UAMME) method seems to be an interesting alternative. In this study, Calendula anthodium UAMME extract composition and antioxidant properties were examined. Several nonionic surfactants, from the group of ethoxy/propoxylated fatty alcohols, were applied in the extraction process. The results were compared with water and water‐ethanoic extracts of marigold flowers. Bioflavonoid compositions of the extracts were determined using ultra‐performance liquid chromatography–diode‐array detector–mass spectrometry (UPLC‐DAD‐MS). Their antioxidant properties were evaluated using free radical‐scavenging activity (2, 2‐Diphenyl‐1‐picrylhydrazyl, DPPH) measurement and Follin's method. Additionally, the structure of the selected flavonoids solubilized in the micelle solution was theoretically simulated using molecular dynamics (MD). The results confirmed that the UAMME method might be an alternative method for the sourcing of the plant extracts rich in natural antioxidants. The results indicated that UAMME extracts showed 19–37% higher DPPH radical inhibition than aqueous extracts. Furthermore, the selection of a suitable surfactant may thus provide the expected composition of the extract. Due to the use as eluents in UAMME, safe raw materials, the obtained marigold flower extracts can be applied as components in the cosmetic and pharmaceutical products.